2007
DOI: 10.1002/micr.20326
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive potential of the lateral arm flap after tumor resection

Abstract: The reconstruction of extended tumor-related defects in different anatomic regions requires a versatile and reliable flap. For many surgeons, the lateral arm flap has become the technique of choice in the reconstruction of small- to medium-sized defects. The aim of this study was to analyze the reconstructive potential of the lateral arm flap after cancer ablation in various indications. Between 1998 and 2006, 14 patients underwent reconstruction with differently composed and designed lateral arm flaps at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…It has predictable and reliable vascular anatomy with constant location of the posterior radial collateral artery. However, Haas et al (2007) had one case of 14 patient's series where a radial collateral artery was absent (Haas et al, 2007). Our study supports the statement of constant anatomy of the flap.…”
Section: Discussionsupporting
confidence: 86%
“…It has predictable and reliable vascular anatomy with constant location of the posterior radial collateral artery. However, Haas et al (2007) had one case of 14 patient's series where a radial collateral artery was absent (Haas et al, 2007). Our study supports the statement of constant anatomy of the flap.…”
Section: Discussionsupporting
confidence: 86%
“…These findings confirmed by other group that had also reported sensory disturbances of the lateral proximal forearm (hypesthesia, paresthesia, hyperesthesia), delayed wound healing, and tendon exposure to be the major complications following LAF harvest. 4,8,17,[20][21][22] Despite the widespread use of the extended technique (ELAF), which facilitates the harvesting of a slim and versatile flap with a longer neurovascular pedicle of up to 12 cm and greater flap size, the donor-site morbidity associated with this extended procedure has been poorly addressed. 17,18,22,23 In contrary to the findings of Graham et al we found scar visibility to be well accepted by the patients in our study with no differences regarding gender (overall satisfaction of 8.2 AE 2.0 in females versus 8.5 AE 1.6 in males).…”
Section: Discussionmentioning
confidence: 99%
“…2 Thanks to its reliable and constant anatomy, good color match and texture, as well as thin design and plasticity the flap has found widespread use for head and neck reconstruction, [3][4][5] as well as for reconstruction of upper and lower extremities. [5][6][7][8][9] Mostly raised as a fasciocutaneous flap, the LAF may also include a segment of the humerus together with parts of the triceps muscle and tendon. Although there is no generally functional limitation in the donor arm, strength and extension can be reduced when the triceps head is transected (harvested as a musculocutaneus flap).…”
mentioning
confidence: 99%